PKM Kelompok Industri Kreatif “Pengrajin Limbah Kayu” untuk Memperkuat Ekonomi Lokal di Kecamatan Mayangan Kota Probolinggo - Ludfi Arya Wardana; Misdiyanto Misdiyanto (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
The aim of the PKM program is aimed at the productive community (UKM) in the district of Probolinggo, Mayangan District. UKM is meant to move in processing wood waste belonging to Mr Eko Nur Widyanto having the address at Mayangan District, Probolinggo City. The problems are namely, the length of the process of designing, cutting and refining wood that is done manually with human power. The lack of optimal network marketing done manually is only an HP device with a Facebook application. The concrete solution made by proponents to overcome the problem is by making and designing lasser wood cutting machines, website marketing and website usage training. The output of this program is lasser wood cutting machines, website marketing, website marketing training.